Cyberbullying Victimization and Perpetration in Adolescents: A Longitudinal Moderated Mediation Model. - Zhao, Yinqiu; An, Wei; Zhang, Yingchao; Yang, Chi; Li, Wenqing; Li, Jianbing; Li, Xiaoyu (Journal of Youth & Adolescence, 2025)
Although cyberbullying victimization significantly impacts cyberbullying behaviors, research on its longitudinal mechanisms and protective factors remains scarce. A total of 1465 Chinese adolescents (52.2% female) with an average age of 16.14 (SD = 0.40) participated in a three-wave longitudinal study with 3-month intervals. Cyberbullying victimization positively predicted cyberbullying perpetration 6 months later, and this effect was mediated by impairment in personality functioning. Mindfulness buffered the predictive effect of cyberbullying victimization on impairment in personality functioning and mitigated the negative impact of impairment in personality functioning on cyberbullying perpetration. Further findings revealed that the indirect effect of impairment in personality functioning was more pronounced when levels of mindfulness were low, and higher levels of mindfulness could disrupt the mediating pathway of impairment in personality functioning between cyberbullying victimization and perpetration. The findings highlighted the importance of promoting the positive development of adolescents' personality functioning and fostering mindfulness skills to reduce cyberbullying among adolescents.